Colonisation of artificial reef balls in Talang-Satang National Park, Sematan, Sarawak - Natasha Nur Amarina, Binti Mohammad Kaie (Universiti Malaysia Sarawak (UNIMAS), 2012)
The primary aim of this study was to determine the percentage cover of hard coral colonisation on the artificial reef balls at Talang-Satang National Park (TSNP). These reef balls were selected because they have been deployed for more than a decade and there is few scientific studies conducted to determine the colonisation of artificial reef balls by hard coral and non-hard coral organisms. The deployment site of the reef balls was at Batu Penyu which is situated within the TSNP area. Belts transect and quadrat frame were used to collect data of percentage cover by hard coral and non-hard coral organisms at each reef ball. Rope was used as a marker to divide the artificial reef balls equally into half and into three zones according to the height of the reef ball for efficiency when in the process of collecting data. Underwater photography was used to ease the identification of hard coral genera. The percentage cover of hard coral and non-hard coral differed among different artificial reef balls. The highest percentage cover of hard coral colonisation was 38% on reef ball no. 3 and the lowest was 2.8% on reef ball no. 8. Overall, the top zone of the reef balls had the highest hard coral colonisation of 74%, followed by 19% at middle zone and 7% at lower zone. Different hard coral genera existed in different zones of reef balls. The most dominant genus at the top, middle and bottom zones is Favia. Growth rate of hard corals differed according to genera. Favia showed the highest growth rate of 0.1 - 10.6 cm2 yr-1 in reef ball no. 17 and Leptoseris had the lowest growth rate of 0 – 0.6 cm2 yr-1 in reef ball no.12. However, the percentage cover of hard coral in reef ball no. 17 was lower, 5.9%, compared to the percentage cover of hard coral in reef ball no. 12 which was 15.6%. The percentage cover by hard corals as well as the dominant coral genera at each zone is postulated to be influenced by the location and duration of deployment, as well as the rate of sedimentation.